IMF History Volume 3 (1945-1965) : Twenty Years of International Monetary Cooperation Volume III; Documents. (International Monetary Fund, 1996)
This paper comprises documents relating to the history of the IMF, including some that preceded the drafting of the Articles of Agreement. The paper highlights that the first draft of Lord Keynes' plan for a Clearing Union was circulated within the British Treasury on September 8, 1941. A fourth draft was given to Ministers on February 11, 1942. The first definitive version of Mr. White's plan for a stabilization fund was a mimeographed draft dated April 1942. This covered both the IMF and the World Bank.